Organoids: their emerging essential role in pathological mechanisms and drug discovery of diabetes and its complications - Xu, Xiaoyu; Zhang, Yunqi; Geng, Yifei; Luo, Yun; Sun, Xiaobo (Frontiers in Pharmacology, 2025)
Diabetes mellitus is a metabolic disease with a high global prevalence, which affects blood vessels throughout the entire body. As the disease progresses, it often leads to complications, including diabetic retinopathy and nephropathy. Currently, in addition to traditional cellular and animal models, more and more organoid models have been used in the study of diabetes and have broad application prospects in the field of pharmacological research. We summarized the organoid models that have been developed for the study of diabetes mellitus and its complications, and describe their sources, establishment and maturation measures with a focus on pancreatic organoids. For the first time, we summarized the contribution of organoids in diabetes and its complications in terms of mechanism studies, drug screening, and cellular replacement therapies, in the hope of providing a feasible direction for personalized medicine and precision treatment of diabetes and its complications. In addition, we discuss the strengths and limitations of organoids in the field of diabetes and its complications. Nowadays, people strongly advocate personalized medicine and precision medicine, and in this regard, organoid technology has advantages that are unmatched by any conventional experimental models. By combing organoid technology with high-throughput technologies, “patient-specific” drug screening can be achieved faster and more accurately. Organoids are also becoming a potential source of transplantable tissues and functional cell types for cellular replacement therapies in regenerative medicine. With further development of assembly and vascularization techniques, organoids will gradually mature and improve. In conclusion, the 3D organoid system greatly complements the existing modeling system and may play a significant role in future basic and clinical research.